Extralinguistic motivation for the functioning of Ukraine`s image in moderm media - Pliasun, Olha (Current issues of Ukrainian linguistics: theory and practice, 2017)
The present article analyzes the internal (national) and external (international) image of Ukraine from a linguistic point of view. The article examines basic communicative functions, correlated with the image of the state, which are distinguished in political science (e.g. identification, idealization, opposition, nominative function, aesthetic function, address function etс. ). The author studies these functions in the projection on the image of Ukraine and reveals that most of the analyzed functions have a common emotive component. The author concludes that medialinguistics as a modern branch of humanitarian knowledge makes it possible to identify the emotive (evaluative) function which is realized in all media texts. The article also deals with investigations of current publications in Ukrainian and foreign media related to the image of Ukraine. The emergence of these publications is connected with the annual Eurovision Song Contest, which this year was held in Kyiv. The primary interest of the given article is the analysis of the principles of creating a high-quality brand of Ukraine that is still the prospect for future research.
Keywords: media, functions of language in media, emotional-estimated connotations, image, extralinguistic motivation of image.